Pharmaceutical promotional literature: opinions of physicians in a tertiary care hospital in Mumbai - Chitnis, Kunal; Limaye, Amod; Bhosale, Manisha (International Journal of Basic & Clinical Pharmacology, 2017)
Backgrounds: The aim of this study was to assess physician’s opinion regarding pharmaceutical promotional material and make an objective assessment about their opinion on current drug promotional methods. Methods: 250 questionnaires were sent to physicians. Questionnaires was based on question assessing physicians opinion about 1) Influence of information provided on their prescription writing pattern. 2) Most common information which they seek for and find missing, was assessed on a Likert scale of 1 to 5 for each type of information 3) Type of promotional material preferred for drug information. 4) Significance of the various types of references cited which was assessed on likert scale of 1 to 5. Results: 207 questionnaires were returned. 59.5 % of the physicians were of the opinion that the information provide in promotional literature mostly influences their prescription. Physicians feel that there is minimal information on adverse drug reaction, comparison with other drugs, price, drug interactions and clinical trial results and contraindications. Likert score of 4.8, 4.7, 4.6, 4.6, 4.5 and 3.9 respectively. 41.07% physicians prefer pamphlets, and leave behind leaflet. Whereas they consider randomized controlled trials, meta-analysis and case controlled or cohort studies as significant references, with likert score 4.9, 4.7, and 4.6 respectively. Conclusion: There is need for strong regulatory infrastructure and monitoring of the content of pharmaceutical promotional activities. Therefore, in the absence of effective regulations and standards physicians should be aware of the risks of using non independent information sources.